Next Generation Stem Cells and their Implications in Cancer Therapy - Ana Sami (Journal of the Pakistan Medical Association, 2023)
Stem cells have been implicated for decades in the treatment of hematological malignancies. These cells when isolated from the bone marrow, adipose tissue, or foetal tissue are deemed as the first generation of stem cells. The turn of the century saw the discovery of the second generation of stem cells such as the human Embryonic Stem Cells (hESCs) and induced Pluripotent Stem Cells (iPSCs). Advances in gene editing technology, in the past decade, have stimulated the rise of next-generation stem cells. Recent studies exploit the tumour tropism, multi-lineage differentiation, and auto-renewal capability of stem cells, and combine it with molecular biology techniques, to create potent anti-cancer therapies. Stem cells have been modified to have low immunogenicity and are thus being used as ‘trojan horses’ for the targeted, intra-tumoral delivery of anti-cancer drugs. continued...